Van ’t Hoff en de roep uit Leipzig in 1887 - van den Berg, Rob (Studium, 2018)
When in June 1887 the Dutch physical-chemist J.H. van ’t Hoff was invited to accept a position at the renowned University of Leipzig, this resulted in a frenzy of activity Amsterdam, where friends, colleagues, students and politicians tried to convince Van ‘t Hoff to stay. Just three weeks later, the municipal authorities made a considerable sum of money available for the construction of a new chemistry laboratory causing Van `t Hoff to give in and remain loyal to his native country. For Van ‘t Hoff the invitation from Leipzig had an unfortunate consequence when four months later, rumours started to circulate that there had never been an offer from Leipzig at all. He was accused of cheating the Municipal Authorities of Amsterdam. Thus, he was obliged to defend his case by going to Germany in person and obtain written proof. The episode illustrates some of the tensions inherent in late nineteenth century Dutch cultural nationalism. The Dutch scientific community craved for international recognition but simultaneously frowned upon those who acted upon such recognition by accepting foreign offers.